Antifungal Activity Testing of Extract and Fractions from Tectona grandis Linn. F Leaves Using the Microdilution Method - Anwar, Irvan -; Malina, Rachma -; Nuralifah, Nuralifah -; Parawansah, Parawansah -; U, Wa Ode Hartasyah (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Teak leaves (Tectona grandis Linn. F) are one of the plants that have empirically been used as antifungal, antioxidant, antibacterial, and antidiabetic agents, due to their content of secondary metabolite compounds including saponins, tannins, alkaloids, and sterols. This research aims to determine the secondary metabolite compounds present in the extract and fractions of teak leaves (Tectona grandis Linn. F) and the antifungal activity of the teak leaf extract and fractions against Candida albicans using the microdilution method. The ethanol extract was fractionated using a partition method with solvents n-hexane, chloroform, and ethyl acetate. Antifungal testing was carried out against Candida albicans using the Broth Microdilution method to measure the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) values. Based on the phytochemical screening results, teak leaves contain alkaloids, phenolics, flavonoids, and terpenoids. The MIC results for the antifungal activity of the ethanol extract, n-hexane fraction, chloroform fraction, and water fraction against Candida albicans were all >500 µg/mL. In the meantime, the MIC and MFC values for ketoconazole 200 mg against Candida albicans were 64 µg/mL. These results indicate that there is a difference in MIC and MFC values between the samples and the positive control (ketoconazole 200 mg), with the antifungal activity of the samples being weaker compared to the positive control